Local structure in a tetravalent-substituent BIMEVOX system: BIGEVOX. Issue 7 (25th January 2022) - Yue, Yajun; Dzięgielewska, Aleksandra; Hull, Stephen; Krok, Franciszek; Whiteley, Richard M.; Toms, Harold; Malys, Marcin; Zhang, Man; Yan, Haixue; Abrahams, Isaac
Abstract : Total neutron and X-ray scattering and 51 V solid-state NMR reveal details of the local structure in the BIGEVOX oxide ion conductor. A non-random deficiency in next-nearest-neighbour vacancy pairs in the 〈100〉 tetragonal direction is found. Abstract : Bi2 ME x l V1− x O5.5−(5− l ) x /2− δ (BIMEVOX, ME = dopant, l = valency) systems are a family of fast oxide ion conductors that show very high ionic conductivity at low and intermediate temperatures. Despite being studied for almost 30 years, the extent of the disorder in these systems has meant that many questions about the detail of the local structure remain unanswered. In this work, reverse Monte Carlo analysis of a combination of synchrotron X-ray and neutron diffraction data has been used to examine the defect structure in the tetravalent-substituent system, Bi2 V1− x Ge x O5.5− x /2− δ . Although the ordered α-phase is seen at room temperature over an extensive compositional range, the incommensurately ordered γ′-phase can be quenched to room temperature at x = 0.35, which on heating above 500 °C, undergoes a transition to the fully disordered tetragonal γ-phase. Germanium is suggested to mainly adopt a tetrahedral coordination environment in both these phases, while vanadium shows different local geometries including tetrahedral, pentacoordinate and octahedral, the relative proportions of which change with temperature. Oxygen vacancies are found to be mainly distributed in equatorial sites around Ge and V, with a higher concentration of apical vacancies in the γ′-phase. A non-random deficiency in next-nearest-neighbour vacancy pairs in the 〈100〉 tetragonal direction is identified, consistent with the known superlattice ordering seen in lower x -value compositions, suggesting short range ordering of oxide ions/vacancies. Such ordering is known to contribute to a lowering of oxide ion conductivity and may well be a factor in lowering the conductivity of the γ-phase BIMEVOXes. These data are supported by 51 V solid state NMR results as well as Raman spectroscopic data, with electrical characterization by A.C. impedance spectroscopy.